2020
DOI: 10.18203/2349-3291.ijcp20201635
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic profile of paediatric patients presenting with acute diarrhea

Abstract: Background: Diarrhea is a public health problem globally, being the 2nd leading cause of death in children under 5 years. Dehydration as well as malnutrition are also serious consequences of diarrhea. This study was carried out with an aim to focus on the clinical and demographic profile of diarrheal patients of pediatric age.Methods: Infants and children aged 6 months to 5 years were analysed for age and gender distribution, chief complaints, feeding practices, nutritional status and assessment of dehydration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Amin et al, [8] (11.53%) of the 76 patients died. Shah et al, [18] in their study observed complete recovery and mortality rate as 66.47% and 16.47% among cases respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Amin et al, [8] (11.53%) of the 76 patients died. Shah et al, [18] in their study observed complete recovery and mortality rate as 66.47% and 16.47% among cases respectively.…”
Section: Discussionmentioning
confidence: 83%